Maternal mortality in Spain and its association with country of origin: cross-sectional study during the period 1999-2015 - V Blagoeva Atanasova; J Arevalo-Serrano; E Antolin Alvarado; Santiago García-Tizón Larroca (BMC, 2018)
Abstract Background The available literature suggests that there are significant differences in maternal mortality according to maternal origin in high income countries. The objective of this study was to quantify the risk of maternal death by maternal origin and region of Spain where the birth occurred and to identify the most important causes of maternal death in our country. Methods An ecological cross-sectional study was conducted that included all deliveries that resulted in maternal survival and cases of maternal death during 1999-2015 in Spain. A descriptive analysis of the maternal mortality rate by maternal origin, region and year of birth was performed. The risk of maternal death was calculated using univariate and multivariate logistic regression analysis, with adjustment for the variables included in the descriptive analysis. Results There were 272 maternal deaths during this period, most of which were due to haemorrhage (63 cases, 23.16%).Women whose continent of origin was South America had the highest adjusted risk of maternal death, with an OR of 3.92 (95% CI 2.75-5.58). The region of Spain with the highest risk of maternal death was Ceuta, with an OR of 12.11 (95% CI 2.02-72.68). Conclusions This study shows that there are inequalities in maternal mortality according to maternal origin and region where labour occurred. These findings highlight the need to establish strategies at the national and European levels to analyse the most relevant causes and risk factors associated with maternal mortality in order to reduce it and pay closer attention in identifying and carefully managing pregnant women from this at risk groups.